2022
DOI: 10.1007/s11356-021-17323-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of ambient air pollutant change on the risk of tuberculosis outpatient visits: a time-series study in Fuyang, China

Abstract: There is growing evidence that air pollution plays a role in TB, but few studies have comprehensively included the six common air pollutants. Our objectives were to investigate the association between short-term exposure to six common air pollutants and the risk of tuberculosis outpatient visits in Fuyang, China, during the period 2015-2020. We combined the two models to explore the effects of exposure to six air pollutants on the risk of tuberculosis outpatient visits, including Poisson generalized linear reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“… 37 A study of ambient air pollutants in Fuyang also showed that O 3 exposure is associated with the risk of TB outpatient visits (RR = 1.049, 95% CI: 1.0012–1.0086, 0-day lag). 38 These findings are consistent with the present study, which confirmed that ozone exposure will increase the risk of TB visit for the following possible reasons: It is thought that this phenomenon may be related to the strong oxidizing properties of ozone. As a strong oxidizing gas, ozone can be oxidized at lower temperatures and can participate in a variety of chemical reactions in the atmospheric environment, and it has a severe irritation of the respiratory tract.…”
Section: Discussionsupporting
confidence: 93%
“… 37 A study of ambient air pollutants in Fuyang also showed that O 3 exposure is associated with the risk of TB outpatient visits (RR = 1.049, 95% CI: 1.0012–1.0086, 0-day lag). 38 These findings are consistent with the present study, which confirmed that ozone exposure will increase the risk of TB visit for the following possible reasons: It is thought that this phenomenon may be related to the strong oxidizing properties of ozone. As a strong oxidizing gas, ozone can be oxidized at lower temperatures and can participate in a variety of chemical reactions in the atmospheric environment, and it has a severe irritation of the respiratory tract.…”
Section: Discussionsupporting
confidence: 93%
“…82 were left after removing duplicates, and then 27 were left after filtering by title. Finally, we accepted 9 articles as the included articles for our research after filtering for the full text and checking references [ 9 , 15 , [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Resultsmentioning
confidence: 99%
“…Low-income to middle-income countries account for the greatest proportion of TB cases (>95%) and some of the highest levels of ambient PM 2.5 (population-weighted annual mean PM 2.5 from ~60% to ~75 µg/m 3 ). 4 5 The association between ambient air pollution and TB disease has attracted a modest but growing body of literature, as we highlighted in a 2019 systematic review, 6 various individual studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and a meta-analysis 27 published subsequent to our review. However, most studies have focused on TB-related outcomes among people who already have TB disease (eg, hospitalisations, mortality) while studies of long-term exposure and new TB disease notifications are comparatively scarce, especially in TB-endemic settings.…”
Section: Open Accessmentioning
confidence: 99%